2015
DOI: 10.18632/oncotarget.6158
|View full text |Cite
|
Sign up to set email alerts
|

Altered microRNA profiles in cerebrospinal fluid exosome in Parkinson disease and Alzheimer disease

Abstract: The differential diagnosis of Parkinson's diseases (PD) is challenging, especially in the early stages of the disease. We developed a microRNA profiling strategy for exosomal miRNAs isolated from cerebrospinal fluid (CSF) in PD and AD. Sixteen exosomal miRNAs were up regulated and 11 miRNAs were under regulated significantly in PD CSF when compared with those in healthy controls (relative fold > 2, p < 0.05). MiR-1 and miR-19b-3p were validated and significantly reduced in independent samples. While miR-153, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
404
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 462 publications
(419 citation statements)
references
References 42 publications
(46 reference statements)
12
404
2
1
Order By: Relevance
“…Our findings were consistent with the results of previous studies showing that STAT3 was negatively regulated by miR-29c-3p in brain tissues (Lei et al 2015). Other studies demonstrated that miR19b3p levels were significantly decreased in the cerebrospinal fluid of AD patients (Gui et al 2015). However, few reports have described target genes of miR19b-3p.…”
Section: Discussionmentioning
confidence: 96%
“…Our findings were consistent with the results of previous studies showing that STAT3 was negatively regulated by miR-29c-3p in brain tissues (Lei et al 2015). Other studies demonstrated that miR19b3p levels were significantly decreased in the cerebrospinal fluid of AD patients (Gui et al 2015). However, few reports have described target genes of miR19b-3p.…”
Section: Discussionmentioning
confidence: 96%
“…Exosomes in the embryonic CSF have also been shown to modulate IGF signalling and promote Neural Stem Cell proliferation (NSC) (Feliciano et al, 2014). Exosomes have been proposed as promising non‐invasive diagnostic tools for cancer (Skog et al, 2008), kidney diseases (Spanu et al, 2014) and neurodegeneration (Liu et al, 2014; Gui et al, 2015) but have not been explored in neonatal development and GMH‐IVH/PHH.…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs impact on α-synuclein expression raises the hypothesis that dysregulated miRNAs in PD patients are responsible for α-synuclein upregulation and/or accumulation. Supporting this idea, several studies have demonstrated that PD patients exhibited dysregulated miRNAs in brain (Kim et al, 2007; Cardo et al, 2013; Miñones-Moyano et al, 2013; Briggs et al, 2015; Hoss et al, 2016), blood (Margis et al, 2011; Martins et al, 2011; Khoo et al, 2012; Botta-Orfila et al, 2014; Burgos et al, 2014), cerebrospinal fluid (CSF; Burgos et al, 2014; Gui et al, 2015; Hossein-Nezhad et al, 2016) and medulla (Liao et al, 2013). …”
Section: Discussionmentioning
confidence: 99%